Raziskave modificiranih kompozitov iz polipropilena in talka - Denac, Matjaž (Kovine zlitine tehnologije, 1999)
Polymer composites based on polypropylene (PP) play an important role in the development of new polymeric materials. Composites of PP, surface treated talc and polymer modifier were investigated. The composites contained 12 vol.% of treated talc and up to 10 vol.% of poly(styrene-b-ethylene-co-butylene-b-styrene) block copolymers (SEBS) of different molecular weights, SEBS grafted with maleic anhydride (SEB-gMA) or PP grafted with maleic anhydride (PP-gMA). Samples were prepared by melt-mixing in a Brabender kneading chamber and were compression molded into plates on a laboratory press. PP/talc/SEBS-gMA and PP/talc/PP-gMA composites were also prepared at different kneading durations. The results of measurement on processing properties (torque), mechanical properties (tensile properties, notched impact strength) and the study of morphology are commented in this article as a function of composition and technological conditions of composites preparation.
Keywords: kompoziti; polipropilen; talk; modifikatorji; mehanske lastnosti